THE MEANINGFULNESS OF LIFE FOR THE ELDERLY WHO LIVE IN NURSING HOMES - Pane, Riem Malini (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2021)
This article contains an analysis of the life meaning of the elderly living in a nursing home. The life meaning is obtained from a theoretical literature review about the life meaning (the results of research from 2009-2020). Based on the theory, the elderly are classified into 4 groups, namely: middle age which is between 45-59 years old, elderly which is between 60-74 years old, old which is between 75-90 years old, and very old which is over 90 years old. The steps in this literature review are identifying key research topics; read abstract of relevant research results; record the reading results by making a literature map (literature map) in sequence; pouring a general view of the research topic based on existing literature, then explaining the originality and importance of the research topic to be carried out in comparison with the existing literature. The study results of this article are useful for guiding the implementation of guidance and counseling for the life meaning of the elderly’s life.